Exploring the alteration of gut microbiota and brain function in gender-specific Parkinson’s disease based on metagenomic sequencing - Zhang, Minna; Zhai, Zhiyuan; Yang, Bo; He, Le; Wang, Jingyi; Dai, Weijie; Xue, Liujun; Yang, Xiaozhong; Feng, Yun; Wang, Honggang (Frontiers in Aging Neuroscience, 2023)
Background The role of the microbiota-gut-brain axis in Parkinson’s disease (PD) has received increasing attention. Although gender differences are known to an essential role in the epidemiology and clinical course of PD, there are no studies on the sex specificity of the microbiota-gut-brain axis in the development and progression of PD. Methods Fresh fecal samples from 24 PD patients (13 males, 11 females) were collected for metagenomic sequencing. The composition and function of the gut microbiota were analyzed by resting-state functional magnetic resonance imaging (fMRI). Gender-dependent differences in brain ALFF values and their correlation with microbiota were further analyzed. Results The relative abundance of Propionivibrio, Thermosediminibacter, and Flavobacteriaceae_noname was increased in male PD patients. LEfse analysis showed that Verrucomicrobial, Akkermansiaceae, and Akkermansia were dominant in the males. In female patients, the relative abundance of Propionicicella was decreased and Escherichia, Escherichia_coli, and Lachnospiraceae were predominant. The expression of the sesquiterpenoid and triterpenoid biosynthesis pathways was increased in male PD patients and was statistically different from females. Compared to the Male PD patients, female patients showed decreased ALFF values in the left inferior parietal regions, and the relative abundance of Propionivibrio was positively correlated with the regional ALFF values. Conclusion Our study provides novel clinical evidence of the gender-specific relationship between gut microbiota alterations and brain function in PD patients, highlighting the critical role of the microbiota-gut-brain axis in gender differences in PD.